Perencanaan dan Pembuatan Dies Permanent Mold Pengecoran Logam dengan Material Besi Cor Ductile (FCD) - Utomo, Cahyo; , Patna Partono, ST., MT (2017)
Metal casting is a process of making a form that is done through several stages ranging from making patterns, molds, melting process, pouring, dismantling, and cleaning castings. The goal of producing products in the form or permanent mold (permanent mold). Permanent prints are molds that can be used repeatedly and are usually made of metal. In the calculation of cavity channel system planning for product volume = 4,808125x10-5 m3, product weight = 0,4 kg, cast time = 1,118 seconds, inlet = 14,6 mm2, drain runner = 29,2 mm2, descending channel = 14,6 mm2, dimensions of top mold size = 340 mm x 200 mm x 30 mm, and dimension of buttom mold size = 340 mm x 200 mm x 70 mm. Solidworks 2014 is used for engineering drawing and the mastercam x5 software is used for planning it is machining process. Machining process using CNC veryical milling machine 3 axis, twin horm travel axis 800x1000x750 xyz. The casting process uses permanent molds more quickly in preparation and foundry products using permanent prints produce products that have very minimal roughness thereby reducing the machining process Keywords: metal casting, permanent molding, solidwork, mastercam, G code, CNC.